B7H6 is a functional ligand for NKp30 in rat and cattle and determines NKp30 reactivity toward human cancer cell lines. Issue 1 (13th December 2018) - Bjørnsen, Elisabeth G.; Thiruchelvam‐Kyle, Lavanya; Hoelsbrekken, Sigurd E.; Henden, Camilla; Saether, Per C.; Boysen, Preben; Daws, Michael R.; Dissen, Erik
Abstract: NK cells kill cancer cells and infected cells upon activation by cell surface receptors. Human NKp30 is an activating receptor expressed by all mature NK cells. The B7 family member B7H6 has been identified as one ligand for NKp30. Several alternative ligands have also been reported, and the field remains unsettled. To this end, we have identified full‐length functional B7H6 orthologs in rat and cattle, demonstrated by phylogenetic analysis and transfection experiments. In cell–cell contact‐dependent assays, chimeric NKp30 reporter cells responded strongly to B7H6 in rat and cattle. Likewise, rat NKp30 expressing target cells induced strong activation of B7H6 reporter cells. Together, these observations demonstrate that B7H6 is conserved as a functional ligand for NKp30 in mammalian species separated by more than 100 million years of evolution. B7H6 and NKp30 are pseudogenes in laboratory mice. The rat thus represents an attractive experimental animal model to study the NKp30‐B7H6 interaction in vivo. B7H6 was widely expressed among human cancer cell lines, and the expression level correlated strongly with the activation of human NKp30 reporter cells. Furthermore, siRNA knockdown of B7H6 abolished NKp30 reporter responses, suggesting that B7H6 is the major functionally relevant expressed ligand for NKp30 on these cancer cell lines. Abstract : B7H6 is conserved as a physiological ligand for NKp30 in rat, cattle, and human, demonstrated in enhanced GFP reporter cell assays using newly identified rat and cattle B7H6 orthologs. NKp30 reporter cell response toward human carcinoma cell lines correlated with B7H6 expression and was abolished upon siRNA knockdown of B7H6.